Factores de riesgo asociados al bajo peso de los recién nacidos del hospital provincial general Julius Doepfner de Zamora. Año 2015 - Gómez Abarca, Leidy Elizabeth (2015)
In the present study it aims to investigate risk factors associated to the low weight of Newborns Provincial General Hospital Julius Doepfner of Zamora. Descriptive, and bibliographic field: for which the following methods were used. The study was made with a sample of 40 mothers with children who had low birth weight, the technique of direct observation with his instrument was applied, the observation guide. That the main sociodemographic characteristics that makes mothers having children of low birth weight, occurs in women aged 13 to 17 years with 62.50% of the basic general education 52,50% , urban with 60.00%; middle social and economic class with 80.00% and civil state free union with 42.50%. Risk factors associated with maternal underweight were type and Environmental conceptional 32% to 37.66%, we find multiple pregnancies with 4.17%, infections during pregnancy with 58.39% and diseases present pregnancy with 37.50%, within the Environmental behavioral factors are: inadequate diet with 25.66%, lack of implementation of immunization with dT 25.66%, absence of controls with 26, 54% and the deficit of consumption of nutritional supplements (iron plus folic acid and calcium) with 22.12%. In implementing the action plan we proceeded to carry out educational activities, producing brochures, posters and home visits to expectant mothers risk visits; what I was helped mothers improve their attitude and responsibility more about taking a responsible pregnancy, decreasing risk factors in mothers who come for care, improving health conditions of mother and newborn preventing future pathologies that occur because of the low weight; concluded that low birth weight is a public health problem, not only for its high morbidity and mortality, but also because of the consequences that may result in adulthood